Patient with a consideration or confirmation of COVID-19 – what every nurse should know - Michalik, Anna; Kolonko, Jolanta; Maciejewski, Dariusz; Kadłubowska, Monika (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2020)
The first case of the disease caused by the coronavirus (SARS-CoV-2) infection, later defined as COVID-19, was identified in December 2019. A mild form of the infection develops in most of the infected people. Some patients present a more severe form of respiratory insufficiency requiring oxygen therapy or the application of mechanical ventilation. Currently it is recommended that interface masks be used, covering the patient’s mouth and nose, as well as breathing circuits that minimise the risk of infection of the medical staff. As the pandemic accelerates, the access of medical staff to personal protective equipment will be a key issue. The aim of the present paper is to discuss the recommendations referring to care provided to patients with consideration or confirmation of SARS-CoV-2, taking into consideration the safety of the medical staff. We expect further modifications of recommendations to the current epidemiological situation.